TORC1 Regulates Developmental Responses to Nitrogen Stress via Regulation of the GATA Transcription Factor Gaf1 - Laor, Dana (mBio, 2015)
The TOR (target of rapamycin [sirolimus]) is a universally conserved kinase that couples nutrient availability to cell growth. TOR complex 1 (TORC1) in Schizosaccharomyces pombe positively regulates growth in response to nitrogen availability while suppressing cellular responses to nitrogen stress. Here we report the identification of the GATA transcription factor Gaf1 as a positive regulator of the nitrogen stress-induced gene isp7(+), via three canonical GATA motifs. We show that under nitrogen-rich conditions, TORC1 positively regulates the phosphorylation and cytoplasmic retention of Gaf1 via the PP2A-like phosphatase Ppe1. Under nitrogen stress conditions when TORC1 is inactivated, Gaf1 becomes dephosphorylated and enters the nucleus. Gaf1 was recently shown to negatively regulate the transcription induction of ste11(+), a major regulator of sexual development. Our findings support a model of a two-faceted role of Gaf1 during nitrogen stress. Gaf1 positively regulates genes that are induced early in the response to nitrogen stress, while inhibiting later responses, such as sexual development. Taking these results together, we identify Gaf1 as a novel target for TORC1 signaling and a step-like mechanism to modulate the nitrogen stress response.